2020
DOI: 10.1055/s-0040-1712529
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Pregnant Women: Case Series from One Large New York City Obstetrical Practice

Abstract: Objective This study aimed to report a case series of pregnant women in New York City with confirmed or presumed coronavirus disease (COVID-19) infection. Study Design Beginning March 22, 2020, all pregnant women from one large obstetrical practice in New York City were contacted regularly to inquire about symptoms of COVID-19 (fever, cough, shortness of breath, malaise, anosmia), or sick contacts. A running log was kept of these patients, as well as all patients who underwent COVID-19 testing. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 3 publications
0
19
1
5
Order By: Relevance
“…Eight studies (95 247 women) compared pregnant populations with non-pregnant populations,2526272829303132 and four studies (2230 women) compared pregnant women with covid-19 versus pregnant women without covid-19 33343536. Forty cohort studies reported on clinical manifestations (13 018 pregnant, 85 084 non-pregnant women),25262728293031323536373839404142434445464748495051525354555657585960616263646566 45 studies reported on covid-19 related maternal outcomes (14 094 pregnant, 85 169 non-pregnant women),2526272829303132353637383940414243454647484950515354555657585961626364656667…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies (95 247 women) compared pregnant populations with non-pregnant populations,2526272829303132 and four studies (2230 women) compared pregnant women with covid-19 versus pregnant women without covid-19 33343536. Forty cohort studies reported on clinical manifestations (13 018 pregnant, 85 084 non-pregnant women),25262728293031323536373839404142434445464748495051525354555657585960616263646566 45 studies reported on covid-19 related maternal outcomes (14 094 pregnant, 85 169 non-pregnant women),2526272829303132353637383940414243454647484950515354555657585961626364656667…”
Section: Resultsmentioning
confidence: 99%
“…In the past, SARS infection was found to increase the risk of fetal distress, and gestational diabetes and pre‐eclampsia are known to be higher in MERS infection, but no such correlation can be established for SARS‐CoV‐2 31 . However, morbidity and mortality were found to be quite low in pregnant patients with COVID‐19 11,12,21,24,28,30,32,33 . In general, a systematic review of the literature shows that pregnant women positive for COVID‐19 with co‐morbidities are more likely to develop complications than those without 34 …”
Section: Maternal Outcomes In Covid‐19mentioning
confidence: 99%
“…A case series from the USA reported adverse outcomes in 28.5% pregnant patients with COVID‐19 including shortness of breath, dyspnea, cardiomyopathy, and moderately reduced left ventricular ejection fractions and hypokinesis, leading to admission to the ICU 39 . However, another case series of pregnant women with confirmed COVID‐19 from the U.S.A reported no pregnancy complications or maternal deaths but reported one fetal demise at 14 weeks of gestation 33 . Recently, the U.S. Centers for Disease Control and Prevention (CDC) presented a surveillance report of women (pregnant and non‐pregnant) with laboratory‐confirmed COVID‐19.…”
Section: Maternal Outcomes In Covid‐19mentioning
confidence: 99%
“…No entanto, uma das pacientes teve morte fetal inexplicada na 14ª semana gestacional, enquanto apresentava sintomas da doença. 9 Ainda em Nova Iorque, ao analisar 3 casos de COVID-19 em gestantes, as mães evoluíram bem, apesar da intubação e da necessidade de ventilação mecânica. A idade gestacional na intubação foi entre 23 e 29 semanas e a duração da ventilação mecânica foi de 3 a 8 dias.…”
Section: Discussionunclassified